2016
DOI: 10.1245/s10434-016-5411-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1800 Robotic and Open Partial Nephrectomies for Renal Tumors

Abstract: In this study, RPN was less morbid than OPN, with lower complications, less blood loss, and a shorter hospital of stay. The intermediate-term oncologic outcomes were similar in the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 28 publications
6
85
3
5
Order By: Relevance
“…The incidence of PA after PN found in the present study (1.2%) was consistent with the rates reported in the largest recent studies in the literature, ranging from 1% to 5% . In addition, these previous studies reported the rate of symptomatic PA, while we reported the incidence of asymptomatic PA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The incidence of PA after PN found in the present study (1.2%) was consistent with the rates reported in the largest recent studies in the literature, ranging from 1% to 5% . In addition, these previous studies reported the rate of symptomatic PA, while we reported the incidence of asymptomatic PA.…”
Section: Discussionsupporting
confidence: 92%
“…The use of partial nephrectomy (PN) for the treatment of RCC has dramatically increased over the past decade, especially for small renal tumours, but also more recently for complex lesions . Haemorrhagic complications are a major concern after PN, and have been reported in 5–10% of patients . The postoperative bleeding risk is mostly related to the presence of pseudoaneurysm (PA), typically occurring within the first 14 days after PN .…”
Section: Introductionmentioning
confidence: 99%
“…Thirty‐four eligible studies included 60 808 patients who underwent PN, of whom 19 638 underwent RaPN with mean age 58.9 years and 41 170 underwent OPN with mean age 58.5 years. Table presents the baseline patient demographics of all enrolled studies.…”
Section: Resultsmentioning
confidence: 99%
“…3,[11][12][13] This present report confirms these prior reports. 14 Peyronnet et al report in this issue of Annals of Surgical Oncology that RPN is associated with favorable perioperative outcomes when compared with OPN. Data were collected from 1800 patients in this retrospective multicenter study, including 937 RPN and 863 OPN.…”
mentioning
confidence: 99%